2014
DOI: 10.1051/epjconf/20146603024
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Asymmetry effects in heavy ion reactions: Complete fusion Vs incomplete fusion

Abstract: Abstract.The Co projectile-target system have been measured for the first time. The recoil catcher technique followed by off-line γ-ray spectroscopy with HPGe detectors was used. The measured excitation functions are compared with the calculations based on the available statistical model codes. The probability of incomplete fusion is found to increase with the projectile energy. Moreover, an attempt has been made to observe the impact of mass-asymmetry on incomplete fusion probability. The effect of α-break-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The detailed description of the experimental procedure etc. used for the 12 C+ 59 Co and 20 Ne+ 51 V systems is given elsewhere [4,5,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description of the experimental procedure etc. used for the 12 C+ 59 Co and 20 Ne+ 51 V systems is given elsewhere [4,5,17].…”
Section: Methodsmentioning
confidence: 99%
“…have been a point of interest even at energies as low as 5 MeV/A. Recent studies report breakup of 12 C, 16 O and 20 Ne into 4 He, 8 Be and 12 C projectile fragments and their incomplete fusion with the target [1][2][3][4][5]. Long back, in 1950, Ghoshal in his famous experiment showed that proton and alpha projectiles forming the same compound nucleus decay similarly and thus corroborate the Bohr compound nucleus assumption [6].…”
Section: Introductionmentioning
confidence: 99%